Drivers of Wetland Utilisation Patterns and The Current Status of Provisioning and Cultural Services In Driefontein and Intunjambili Wetlands, Zimbabwe - Tatenda Musasa; Thomas Marambanyika (Research Square, 2022)
The study assesses drivers of wetland utilisation patterns and the current status of provisioning and cultural services in Driefontein and Intunjambili wetlands, Zimbabwe. A total of 280 questionnaires were administered together with semi-structured interviews conducted with key informants in the two wetlands. Qualitative data obtained through the questionnaire survey and key informant interviews were analyzed using the content analysis method. The majority of the households in Driefontein (86%) and Intunjambili (75%) indicated that there is no change in wetland utilisation patterns over the past decade as horticultural activities remain the predominant activity. Most households (90%) in Intunjambili indicated that the availability of water is the major factor influencing wetland use. This was different from Driefontein where market availability for horticultural products (66%) was the main reason for wetland use. Land use land cover (LULC) changes established through analysis of remotely sensed imagery for the years 1999, 2009 and 2019 indicate an increase in the spatial extent of the cultivated area, bare land and a decrease in the area covered by water. Results also show that the two wetlands are providing water for drinking and crop cultivation, pasture for livestock grazing and opportunities for academic incursions. Overall, the two wetlands provide essential provisioning and cultural services hence the need for wise use and proper management to prevent their degradation and possibly loss of human benefits